Selective serotonin reuptake inhibitors for amblyopia treatment: a systematic review and meta-analysis of randomized controlled trials - Shamsher, Ehtesham; Saccaro, Luisa; Pungirum, Victor Barreiros; Tran, Nghi Bao; Alghaith, Omar A. H. A.; Khabazianzadeh, Fatemeh; Bridge, Holly; Ip, I. Betina (Frontiers in Neurology, 2025)
IntroductionAmblyopia is a neurodevelopmental visual disorder treated with occlusion or pharmacological penalization of the dominant, non-amblyopic eye in early childhood. After early childhood, efficacy of occlusion therapy is limited due to a reduction in neuronal plasticity, and no mainstay clinical treatment is available. Selective serotonin reuptake inhibitors (SSRIs) have been hypothesized to enhance neuroplasticity in the adult brain, thereby facilitating improvements in amblyopia. We aimed to perform a systematic review and meta-analysis evaluating the effect of SSRIs on patients with amblyopia.MethodsWe systematically searched Pubmed, EMBASE, and Cochrane Central for randomized controlled trials (RCTs) and controlled observational studies comparing an SSRI with placebo in patients with amblyopia. Outcomes of interest were visual acuity (VA) change and visual evoked potential (VEP) change (P100 amplitude and latency). Statistical analysis was performed using the web version of RevMan by calculating the mean difference between groups (MD). Heterogeneity was assessed with Cochrane Q test and I2 statistics.ResultsFour RCTs and 139 patients were included. 55% patients received SSRIs. Three studies used fluoxetine and one study used citalopram as the intervention. While SSRIs use statistically improved VA (MD 0.09 logMAR, 95% CI 0.04–0.14, p = 0.0004), the extent of improvement was not clinically significant. SSRIs did not have any effect on VEPs.ConclusionWhile SSRIs significantly improved VA in patients, the increase was not clinically significant as it represents less than one line of improvement on the Snellen chart. Given the minimal change in VA, it may be necessary to combine SSRIs with other modalities of intervention to demonstrate a clinically significant effect. Secondary endpoints that capture effects at the level of the retina and the brain would provide knowledge of physiological mechanisms that can improve future therapies.Systematic review registrationCRD42025633077, https://www.crd.york.ac.uk/PROSPERO/view/CRD42025633077.